Mitochondrial antiviral signaling protein: a potential therapeutic target in renal disease - Wu, Meng; Pei, Zhiyin; Long, Guangfeng; Chen, Hongbing; Jia, Zhanjun; Xia, Weiwei (Frontiers in Immunology, 2023)
Mitochondrial antiviral signaling protein (MAVS) is a key innate immune adaptor on the outer mitochondrial membrane that acts as a switch in the immune signal transduction response to viral infections. Some studies have reported that MAVS mediates NF-κB and type I interferon signaling during viral infection and is also required for optimal NLRP3 inflammasome activity. Recent studies have reported that MAVS is involved in various cancers, systemic lupus erythematosus, kidney diseases, and cardiovascular diseases. Herein, we summarize the structure, activation, pathophysiological roles, and MAVS-based therapies for renal diseases. This review provides novel insights into MAVS's role and therapeutic potential in the pathogenesis of renal diseases.